2010
DOI: 10.1172/jci40269
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy enhances tumor cell susceptibility to CTL-mediated killing during cancer immunotherapy in mice

Abstract: Cancer immunotherapy faces a serious challenge because of low clinical efficacy. Recently, a number of clinical studies have reported the serendipitous finding of high rates of objective clinical response when cancer vaccines are combined with chemotherapy in patients with different types of cancers. However, the mechanism of this phenomenon remains unclear. Here, we tested in mice several cancer vaccines and an adoptive T cell transfer approach to cancer immunotherapy in combination with several widely used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
347
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(365 citation statements)
references
References 39 publications
11
347
2
5
Order By: Relevance
“…109 Paclitaxel, cisplatin and doxorubicin sensitize tumor cells to CTLs by rendering them permeable to granzyme B via upregulation of mannose-6-phosphate receptors on tumor cell surface. 110 Furthermore, CTX sensitizes tumor cells to TRAIL-dependent CD8 T-cellmediated immune attack, 111 suggesting that TRAIL-mediated tumor cell killing contributes to immunogenic TCD. 112 Platinum derivatives and dacarbazine were shown to stimulate the expression of ligands for NKG2D, an NK cellactivating receptor, resulting in augmented NK-cell cytotoxicity and IFN-g production.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
“…109 Paclitaxel, cisplatin and doxorubicin sensitize tumor cells to CTLs by rendering them permeable to granzyme B via upregulation of mannose-6-phosphate receptors on tumor cell surface. 110 Furthermore, CTX sensitizes tumor cells to TRAIL-dependent CD8 T-cellmediated immune attack, 111 suggesting that TRAIL-mediated tumor cell killing contributes to immunogenic TCD. 112 Platinum derivatives and dacarbazine were shown to stimulate the expression of ligands for NKG2D, an NK cellactivating receptor, resulting in augmented NK-cell cytotoxicity and IFN-g production.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
“…Although 16 of 48 patients discontinued the trial because of adverse effects (AEs) and 4 fatalities occurred, treatment with nivolumab 3 mg/kg with ipilimumab 1 mg/kg achieved a higher objective response rate (ORR) regardless of histology type (29%). At 2016 ASCO, 14,20 77 patients randomly assigned into 2 cohorts either received nivolumab 3 mg/kg q2w with ipilimumab 1 mg/kg every 12 weeks or 6 weeks (38 and 39 patients, respectively). The results showed that patients in the ipilimumab every 12 weeks cohort seemed to have better response to treatment with prolonged median progression-free survival (PFS: 8.1 vs. 3.9 months).…”
Section: Combination Strategiesmentioning
confidence: 99%
“…100 This finding was reinforced by other authors who have observed that the in vitro treatment of murine colon cancer cells with low concentrations of PTX or doxorubicin increased their sensitivity to specific anti-p53 CTL. 80 Authors obtained similar results treating human lung cancer cells (H332). Although no direct effect of PTX on murine lymphocytes was observed, doxorubicin negatively affected cell toxicity 80 and human peripheral blood cells were sensitive to drug treatment.…”
Section: Immunomodulatory Effects Of Ultra-low Concentrations Of Chemmentioning
confidence: 66%
“…Similar results were observed in the tumor progression of a breast cancer model, which growth was delayed in contrast with the poor activity of drug alone. 80 Immunotherapy based on the administration of cytokines is one of the goals of several groups. It was observed, for instance, that the incubation of tumor cells with granulocytemacrophage colony-stimulating factor (GM-CSF) induces cell surface modification.…”
Section: Immunomodulatory Effects Of Ptx and Combination With Immunotmentioning
confidence: 99%
See 1 more Smart Citation